Часовая Башня: [роман] / Н. В. Щерба - Щерба Наталья Васильевна (Часодеи, 2015)
Экземпляры: детская б-ка (20151002) / Инвентарный номер: 44865 / Цена: 350 / Сис.шифр: 84Р6 / Авт.знак: Щ 61 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6